The Effect of Reciprocal Teaching Styles on the Ability to Hit Drop Shot in Badminton Games for SMA Negeri 1 Tahuna Students - Marnex Willner Berhimpong; Christianti Anggraini Motto; Suandi Selian (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
In teaching, every teacher must master the methods and teaching materials that will be taught to their students. The ability to dribble will be better if students carry out the exercises regularly and are taught to use the correct teaching style and this style is adjusted to the objectives and time available. Operationally the objectives of this study are: The influence of reciprocal teaching style on the ability to hit the drop shot in badminton games for students of SMA Negeri 1 Tahuna. The data presented in this study are the results of measuring the ability to drop shoot in badminton before and after being given treatment in the form of reciprocal teaching styles for the experimental group and pre-test and post-test data for the control group that were not given treatment. The average drop shoot ability of the experimental group is greater than the average drop shoot ability of the control group. This means that the increase in drop shoot ability is really the result of the treatment in the form of a reciprocal teaching style given for eight weeks.